Hox genes and evolution - Hrycaj, Steven M. (F1000Res, 2016)
Hox proteins are a deeply conserved group of transcription factors originally defined for their critical roles in governing segmental identity along the antero-posterior (AP) axis in Drosophila. Over the last 30 years, numerous data generated in evolutionarily diverse taxa have clearly shown that changes in the expression patterns of these genes are closely associated with the regionalization of the AP axis, suggesting that Hox genes have played a critical role in the evolution of novel body plans within Bilateria. Despite this deep functional conservation and the importance of these genes in AP patterning, key questions remain regarding many aspects of Hox biology. In this commentary, we highlight recent reports that have provided novel insight into the origins of the mammalian Hox cluster, the role of Hox genes in the generation of a limbless body plan, and a novel putative mechanism in which Hox genes may encode specificity along the AP axis. Although the data discussed here offer a fresh perspective, it is clear that there is still much to learn about Hox biology and the roles it has played in the evolution of the Bilaterian body plan.